New species and new records of gelechiid moths (Lepidoptera, Gelechiidae) from southern Siberia - Bidzilya, Oleksiy; Nupponen, Kari (Zootaxa, 2018)
Noteworthy records of 23 species of the family Gelechiidae from southern Siberia are reported. The following seven new species are described: Metzneria transbaikalica Bidzilya, sp. nov., Istrianis jaskai Bidzilya, sp. nov., Teleiopsis kyraensis Bidzilya, sp. nov., Athrips nigrilineella Bidzilya & K. Nupponen, sp. nov., Filatima multicornuta Bidzilya & K. Nupponen, sp. nov., Lutilabria pallidella K. Nupponen & Bidzilya sp. nov. and Caryocolum unicolorellum Bidzilya, sp. nov. Two new synonyms are established: Filatima bidentella Bidzilya, 1998 syn. nov. of Filatima asiatica Sattler, 1961; Filatima autocrossa Meyrick, 1937 syn. nov. of Filatima pallipalpella Snellen, 1884. Lutilabria kaszabi Povolný, 1978 is re-described based on additional material. The hitherto unknown females of Filatima asiatica, F. karsholti Ivinskis & Piskunov, 1989, F. sciocrypta (Meyrick, 1936) and Athrips kerzhneri Piskunov, 1990 are described. Dirhinosia interposita Bidzilya & Budashkin, 2015, Scrobipalpa flavinerva Bidzilya & Li, 2010, Scrobipalpa sinica Bidzilya & Li, 2010 and Filatima karsholti are recorded from Russia for the first time. Nine species are recorded for the first time from different regions of Siberia. Female brachyptery in Filatima Busck, 1939 and Lutilabria Povolný, 1965 is reported for the first time.